Keterkaitan Karakteristik Demografi dengan Depresi pada Keluarga Pasien Stroke di RSUD Dr. Haryoto-Lumajang - Ifka Wardaniyah; Muhamad Zulfatul A'la; Siswoyo Siswoyo (UPT Percetakan dan Penerbitan Universitas Jember, 2023)
Stroke could cause disability and death for sufferers. Stroke patients with family assistance have to maintain daily activities. Family of stroke patients who gives long-term care have experience problems especially depression. The purpose of this study was to analyze the relationship between demographic characteristics and depression of family with stroke patient using cross sectional aprroach. The sampling technique was consecutive sampling with a total sample of 65 respondents determined using G*Power. The measuring instruments used demographic characteristic questionnaire and Beck Depression Inventory II (BDI II). This study found the prevalence of depression in families of stroke patients were 24 (36.9%) depressed and 41 (63.1%) not depressed. Moreover, there were no relation between characteristics (gender, age, education status, employment status, relationship with patients, stroke attack, duration of care) and depression in family with stroke patients (p>0.05). Depression could occur because of internal and external factors in a person depending on each person’s problem solving ability. Further research, should be conducted to examine the intervention of nursing that are appropriate for preventing the occurrence of depression in family of stroke patients.